2011
DOI: 10.1111/j.1365-2788.2011.01490.x
|View full text |Cite
|
Sign up to set email alerts
|

Williams syndrome: a relationship between genetics, brain morphology and behaviour

Abstract: Our findings are then discussed with reference to the Rakic radial-unit hypothesis of cortical development, arguing that WS gene deletions may spare Cth yet affecting the number of founder cells/columns/radial units, hence decreasing the SA and CV. In essence, cortical brain structure in WS may be shaped by gene-dosage abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 84 publications
(82 reference statements)
2
13
0
Order By: Relevance
“…In spite of small cohorts, these investigations of pediatric populations point to reductions in gray matter volumes in occipital and parietal lobes in Williams syndrome [Boddaert et al, 2006;Campbell et al, 2009] similar to that reported in the adult population, and increased gray matter volumes in frontal and temporal regions [Campbell et al, 2009]. Fahim et al [2012] recently compared CT and SA between 10 children with Williams syndrome and 12 typically developing controls (age range 2.3-14.6 years), and found an overall preservation of CT and reductions in SA. Although a picture of brain structure in children and adolescents with Williams syndrome has begun to emerge, little is known about the developmental trajectories of brain anatomy in Williams syndrome overall, and specifically of CT and SA.…”
Section: Neuropsychiatric Geneticsmentioning
confidence: 85%
See 3 more Smart Citations
“…In spite of small cohorts, these investigations of pediatric populations point to reductions in gray matter volumes in occipital and parietal lobes in Williams syndrome [Boddaert et al, 2006;Campbell et al, 2009] similar to that reported in the adult population, and increased gray matter volumes in frontal and temporal regions [Campbell et al, 2009]. Fahim et al [2012] recently compared CT and SA between 10 children with Williams syndrome and 12 typically developing controls (age range 2.3-14.6 years), and found an overall preservation of CT and reductions in SA. Although a picture of brain structure in children and adolescents with Williams syndrome has begun to emerge, little is known about the developmental trajectories of brain anatomy in Williams syndrome overall, and specifically of CT and SA.…”
Section: Neuropsychiatric Geneticsmentioning
confidence: 85%
“…Based on previous studies [Thompson et al, 2005;Luders et al, 2007;Fahim et al, 2012;Meda et al, 2012], we predicted that overall CT would be increased and SA would be reduced in Williams syndrome compared to healthy, age-and sexmatched controls. Furthermore, from a developmental perspective, we sought to evaluate differences in CT and SA between Williams syndrome and controls across two age groups: youth (age range 6.6-18.9), and adults (age range 20.2-51.5).…”
Section: Neuropsychiatric Geneticsmentioning
confidence: 97%
See 2 more Smart Citations
“…Benign types of these tumours were rarer than 0.5% (1). They can present with chronic cough, progressive dyspnoea and obstructive symptoms but they are usually asymptomatic since the mass lesion grows significantly (1).…”
Section: Initial Bronchoscopic Treatment Of Tracheal Schwannoma: a Ramentioning
confidence: 99%